2016
DOI: 10.1038/srep23801
|View full text |Cite
|
Sign up to set email alerts
|

A computational simulation of the effect of hybrid treatment for thoracoabdominal aortic aneurysm on the hemodynamics of abdominal aorta

Abstract: Hybrid visceral-renal debranching procedures with endovascular repair have been proposed as an appealing technique to treat conventional thoracoabdominal aortic aneurysm (TAAA). This approach, however, still remained controversial because of the non-physiological blood flow direction of its retrograde visceral revascularization (RVR) which is generally constructed from the aortic bifurcation or common iliac artery. The current study carried out the numerical simulation to investigate the effect of RVR on the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…Image-based CFD simulation has been widely accepted as an alternative approach to study the hemodynamic properties, due to the difficulty of studying the outcome directly in vivo . Hemodynamic indicators could help to evaluate the efficacy of treatment options, such as the Norwood procedure ( 34 , 35 ), thoracic endovascular aortic repair and hybrid treatment procedure ( 13 , 15 ). However, hemodynamic simulation might be limited for that focuses on the vessel wall motion or that aims to investigate the mechanical interaction between vessel wall and the stent grafts due to the simplification of rigid wall in hemodynamic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Image-based CFD simulation has been widely accepted as an alternative approach to study the hemodynamic properties, due to the difficulty of studying the outcome directly in vivo . Hemodynamic indicators could help to evaluate the efficacy of treatment options, such as the Norwood procedure ( 34 , 35 ), thoracic endovascular aortic repair and hybrid treatment procedure ( 13 , 15 ). However, hemodynamic simulation might be limited for that focuses on the vessel wall motion or that aims to investigate the mechanical interaction between vessel wall and the stent grafts due to the simplification of rigid wall in hemodynamic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…So we first calculated the corresponding pressure drop from the supraceliac artery to each visceral organ in terms of the flowrate ratio for a healthy AA model, then we applied the same perfusion pressure to the corresponding visceral organ for the RVRs. In another words, assuming that the pressure at the supraceliac artery was 100 mmHg, the outlet pressure at each visceral artery was then defined taking into account the corresponding pressure drop for a healthy AA model[ 12 ]. The iliac outlet pressure was selected so that the entire flow rate was the same as that for the healthy one.…”
Section: Model and Methodsmentioning
confidence: 99%
“…However, CIAs are indicated to provide the unique inflow of RVR because of the whole infrarenal aortic artery lesion with Crawford II/III/IV TAAA[ 10 , 11 ]. Our last paper revealed that an non-physiological hemodynamics of RVR from the infrarenal abdominal aortic or CIA will induce some potential risks to the host artery and the visceral organs[ 12 ]. However, the hemodynamic effects of RVR for Crawford type II/III/IV TAAA is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In most reports in the literature, the retrograde approach has been used, with distal aortic or iliac artery inflow. According to a computational study by Wen et al, 28 retrograde visceral revascularization (RVR) from the distal aorta may reduce flow in the iliac artery and predispose the distal aorta to aneurysm formation. On the contrary, RVR from the iliac artery did not alter the flow in the limbs but reduced the flow in the visceral vessels and changed the flow in the iliac artery, predisposing to stenosis of the bypass grafts.…”
Section: Hybrid Taaa Repairmentioning
confidence: 99%